KINERJA LINGKUNGAN DAN KINERJA SAHAM PERUSAHAAN PUBLIK DI INDONESIA - Negina Putri; Estri Mufridatul Hikmah (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
Environmental performance carried out by the company can be an indicator of how well the company carries out the level of environmental management. This study aimed to examine the effect of environmental performance on the stock performance of public companies listed in the SRI KEHATI index in the Indonesia Stock Exchange. The samples consisted of 22 companies listed on the Indonesia Stock Exchange and included in the index during 2017-2019. Environmental performance is measured through environmental performance reporting that refers to the Global Reporting Initiative (GRI) standard Series 300. The standard consists of 8 components. Meanwhile, stock performance is measured by the value of Cumulative Abnormal Return (CAR). The data were processed using regression after testing the classical assumptions previously. The results showed that companies with a good stock performance report had a good environmental performance, as indicated by the t-test value, which all had a positive direction. Besides, the components of energy, biology, waste, and environmental compliance had statistically significant effects. This research implied that companies and investors need to pay attention to the efforts to submit environmental performance following the standards because it is proven to be able to influence firm value through its stock performance. Keywords: sustainability reporting, company value, GRI standard Series 300, CAR, company performance